1975
DOI: 10.1002/jsfa.2740260112
|View full text |Cite
|
Sign up to set email alerts
|

Trace metal content of chicken eggs

Abstract: Results are presented for the levels of cadmium, chromium, cobalt, copper, iron, lead, manganese, mercury, nickel and zinc in each of 100 shelled chicken egg samples, as determined by atomic absorption spectrophotometry. The range and mean for each of the trace metals are as follows: cadmium, n.d. to 0.03 and 0.01 parts/million; chromium, n.d. to 0.15 and 0.06 parts/million ; cobalt, n.d. to 0.06 and 0.03 parts/million; copper, 0.54 to 0.88 and 0.66 partsjmillion; iron, 17.1 to 27.5 and 21.5 parts/million; lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
2

Year Published

1980
1980
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 25 publications
1
13
2
Order By: Relevance
“…Se levels for chicken egg were similar to those reported by a recent work of Pappa et al [19] in Greece and those reported in other European countries [20][21][22]. Our results comply partly with those of Kirkpatrick and Coffin [23] who have measured the content of chicken eggs in ten trace minerals through the use of flame atomic absorption spectroscopy. In our study, Cu values were double; Zn and Mn values were higher, while Cr and Cd values were similar to the values reported by the previous study.…”
Section: Discussionsupporting
confidence: 95%
“…Se levels for chicken egg were similar to those reported by a recent work of Pappa et al [19] in Greece and those reported in other European countries [20][21][22]. Our results comply partly with those of Kirkpatrick and Coffin [23] who have measured the content of chicken eggs in ten trace minerals through the use of flame atomic absorption spectroscopy. In our study, Cu values were double; Zn and Mn values were higher, while Cr and Cd values were similar to the values reported by the previous study.…”
Section: Discussionsupporting
confidence: 95%
“…Previous reports have described low amounts of Cd accumulation in eggs (Ishizaki et al, 1970;Kirkpatrick & Coffin, 1975). Leach et al (1979) demonstrated that the Cd content in eggs i s very low after oral administration of Cd.…”
mentioning
confidence: 97%
“…However, no significant difference was observed in the mean concentrations of Ni in eggs from farms within the Asaba, Benin and Onitsha zones. Kirkpatrick and Coffin (1975) reported Ni levels ranging from not detected to 0.35 mg g À1 in eggs collected from the different regions of Canada. Van Overmeirer et al (2006) reported Ni levels ranging from 0.0017 to 0.085 mg g À1 in eggs from private and commercial farms in Belgium.…”
Section: Resultsmentioning
confidence: 96%
“…Van Overmeirer et al (2006) reported 9.74 and 11.5 mg g À1 as mean concentrations of Zn in eggs from private and commercial farms, respectively, in Belgium. Kirkpatrick and Coffin (1975) recorded Zn levels in the range of 10.7-18.4 mg g À1 in eggs from different localities in Canada. Average contents of 9.77-13.75 mg Zn g À1 have been reported (Zmudzki et al 1992;Dobrzanski et al 1999;Fakayode and Olu-Owolabi 2003).…”
Section: Resultsmentioning
confidence: 99%